Survey Empiris Terapi Komplementer Pada Ibu Hamil : Mixed Methods Study - Samida, Samida -; Mardison, Lidya; Syukri, Rahmat (Universitas Fort De Kock Bukittinggi, 2024)
Background: Pregnancy is a period that starts from the process of conception (conception) until before the fetus is born and is a physiological state. Improper handling of pregnant women is caused by less or even no ANC treatment during pregnancy. Many efforts can be made by pregnant women to overcome various complaints during pregnancy, one of which is complementary therapy or traditional medicine passed down from the family and culture of the local community. This study aims to conduct an empirical survey of complementary therapies for pregnant women in the work area of Muara Tembesi Health Center. Methods: This type of research is Mixed methods with an Exploratory design which was carried out in November 2023 with the population of all pregnant women and the local community. This sampling uses purposive sampling techniques with quantitative samples of 50 respondents and qualitative 16 informants. The instruments used are interview protocols and questionnaires. Qualitative data analysis using the Miles & Huberman model and univariate quantitative data analysis. Results: The research results show that the common complaints of pregnant women are nausea, vomiting, fatigue, dizziness, heartburn, emotional disturbances, aches or pain in the legs, back and waist and leg edema. Meanwhile, the complements used by pregnant women are adjusted to the type of complaints experienced, including consumption of boiled ginger water (78%), lemongrass infusion (34%), betel infusion (8%), half-cooked free-range chicken eggs (60%), fruit and vegetables ( 56%), and massage therapy (52%). Conclusion: It is expected that pregnant women can apply complementary therapies in health services in the form of integrative services.